PENGARUH KELOMPOK SEBAYA TERHADAP PRESTASI DAN DEVIASI DI SMK N 1 TALUK KUANTAN KABUPATEN KUANTAN SENGINGI - Sahria, Eli; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Education is a process or a system consisting of several components. Smooth running of the smooth component will bring no educational process. Educational success is certainly not out of learning to improve learning outcomes in need of motivation in learning. In terms of education programs, practices in vocational subjects received a larger portion of the theoretical lessons, while in high school otherwise. From the description can be explained that even though the school is a vocational-oriented world of work and one of my goal to provide supplies to students ready to enter the world of work, vocational graduates can also continue their education to a higher level in accordance with vocational majors or even lain.Adapun phenomenological available on the student / student is their absence of competing well in their own group or between groups in order that he or his group looks the best, sometimes they taunted each other, each harbored feelings that are either negative or positive, is negative in intent is the distaste among friends or between groups, in addition, the authors also found the following symptoms: a). How do the characteristics of the peer group in SMK Negeri 1 TalukKuantanKuantan District Singingi? b). How peer relationships and the achievement of students in SMK deviation 1 TalukKuantanKuantan District Singingi? Aim of research is to determine whether there is development of SMK N 1 taluksekoalahkuantan to achievement or even higher deviation and to investigate how the interaction of social relations , motivation, the influence of the school environment or outside of school (extracurricular). To obtain the necessary data in this study, the authors collected data by direct down spaciousness or observation. The study was conducted through random sampling, relying on secondary data and primary data from respondents to the objects in question through questionnaires and in-depth interviews. In accordance with the problems and objectives to be answered, then do the processing qualitative data that is processed with the use of tables and explanations deskriptifHasil research shows that students in the more dominant groups to want to perform better than other friends, this competition also had a positive impact for students in this class XI. Deviation (deviation) occurs as students fight with his average of respondents' answers were never answered by the number of 30 respondents or 100%, ditching school average respondent answered "sometimes-kanga" with the number 23 or 76 respondents, 67%, lie average respondent answered "sometimes", smoking in school average "never" to the number of 21 respondents or 70.00% of the respondents, drinking alcohol mean "never" to the number of 27 respondents or 90% , and watching porn with friends the average respondent answered "sometimes" with a number of 16 respondents or 53.33%.Keyword: Education, Accomplishments, Deviation.